IT Valuation Deployer Information System Implementation at PT Telkom Indonesia Access B3E Approach: IT Valuation Deployer Information System Implementation at PT Telkom Indonesia Access B3E Approach - Muhammad Aliy Zulfanny; Wahyu Rudianto (Institute of Computer Science (IOCS), 2020)
Telkom Akses is a subsidiary of Telkom which is a state-owned company in Indonesia. Telkom Akses is engaged in telecommunications, especially the construction of Optical Fiber, Construction to Design Data and Inventory activities. In carrying out optical fiber development, Telkom Access has an information system called Deployer. Deployer's information system documents all activities from surveying, construction to inventory. This involves all parts of Telkom access, especially in the construction division. To get valid information about this information system, it is effective and efficient for the company as well as the feasibility of developing it. So, this study was conducted entitled